Prevalence and correlates of adherence to the combined movement guidelines among Czech children and adolescents - Rubín, Lukáš; Gába, Aleš; Dygrýn, Jan; Jakubec, Lukáš; Materová, Eliška; Vencálek, Ondřej (BMC public health, 2020)
BACKGROUND: There are limited studies on the prevalence of adherence to the combined guidelines for physical activity (PA), sedentary behavior, and sleep in children and adolescents. Moreover, little is known about correlates of adherence to the guidelines. Therefore, the main aim of this study is to examine the prevalence and identify the correlates of adherence to the combined movement guidelines among children and adolescents. METHODS: A total of 355 children aged 8-13 years (44% boys) and 324 adolescents aged 14-18 years (43% boys) from the Czech Republic participated in this study. PA and sleep duration were estimated using multi-day 24-h raw data from wrist-worn accelerometers. Recreational screen time was parent proxy-reported in children and self-reported in adolescents. Seventeen potential correlates were grouped into three homogenous categories for biological and cognitive, behavioral, and family correlates. The multi-level multivariable logistic regression was applied to identify correlates of adherence to combined movement guidelines and to specific combinations of any of two recommendations. RESULTS: Approximately 6.5% of children and 2.2% of adolescents met all recommendations of the combined movement guidelines. In children, girls (OR = 0.4; 95% CI = 0.1-0.9) and participants with overweight or obese fathers (OR = 0.3; 95% CI = 0.1-0.7) had significantly lower odds of adherence to the combined movement guidelines. Additionally, children had higher odds of meeting specific combinations of two recommendations if they reported regular fruit and vegetable intake, participated in organized PA, or if their fathers had a university degree. Meanwhile, paternal overweight and obesity, and high sleep efficiency were associated with lower odds of meeting specific combinations of recommendations. In adolescents, sex, fruit and vegetable intake, organized PA, and active play were correlates of meeting specific combinations of any two recommendations. CONCLUSIONS: A low proportion of children and adolescents met the combined movement guidelines and several correlates related to family were identified. Family is a key source of influence for healthy movement behaviors during childhood and adolescence.
Keywords: Guideline Adherence; Sedentary Behavior; Female; Prevalence; dítě; čas strávený před obrazovkou; ženské pohlaví; sedavý životní styl; průřezové studie; Adolescent; lidé; cvičení; prevalence; Cross-Sectional Studies; spánek; Male; Czech Republic; Sleep; Česká republika; Child; mužské pohlaví; Exercise; Screen Time; mladiství; dodržování směrnic; Humans